Die Begegnung am Brunnen (Joh 4.4–42) im Licht der „Schrift": Überlegungen zu den Samaritanern im Johannesevangelium*. (26th February 2015) - Förster, Hans
<x content-type="archive" xml:space="preserve">Abstract</x> Within the narrative of John 4.4–42 (the Samaritan woman at the well) the fact is mentioned that 'Jacob's well' had been given to his son Joseph (John 4.5). By calling Jacob 'our father' (John 4.12), the woman claims for the Samaritans a direct lineage from Jacob via Joseph. The Samaritans are designated as 'children of Israel' and members of the tribes of Ephraim and Manasseh (i.e. the 'house of Joseph'). The genealogy is embedded in a motif occurring in Scripture (the encounter at the well). Thus, it is questionable whether the passage of the woman at the well can primarily be seen as 'mission among gentiles'. The narrative focus of the passage seems to point to a mission among the 'children of Israel'.